"Like or Rely? Korelasi Content Likeability dan Content Credibility terhadap Consumer Acceptance pada Advertising Product Placement - Hardany Hardany; Sarah Samaria Najoan (Inter Komunika, 2022)
Technological growth in the era of globalization is increasing, not only is technology increasingly sophisticated, but culture is also easily spread. The Korean wave emerged in Southeast Asia in the 2000s covering several cultural contents such as music (K-pop), fashion (K- fashion), and television (K-drama) which are related to each other. Endless Korean Drama Vincenzo is a Korean drama that features a product or has a product placement, namely Kopiko candy, one of the companies from Indonesia trying to implement an advertising strategy. The research objective was to determine the relationship between content likeability and content credibility with Kopiko's product placement. This study uses Laswell's communication theory, cultivation theory as well as content likeability, credibility and product placement. The method used is quantitative by distributing questionnaires to 100 respondents. In this study, validity and reliability tests were carried out as a test for analyzing respondent data, as well as using a linear regression test to see the relationship between variables. The results of this study concluded that content likeability and content credibility can be the selling points of a product shown through a film or drama that places a product or product placement to be able to influence viewers who like Korean films or dramas Vincenzo.